The Influence of Multicultural Education on the Tolerance Attitudes of Eighth-Grade Junior High School Students - Gracianus Edwin Tue P. Lejap; Yakobus Q. A. Beraheng (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to determine the effect of multicultural education on the tolerance attitudes of class VIII students at the UPTD of SMP Negeri 16 Kupang City in the 2024/2025 Academic Year. The research used a quantitative approach with a simple linear regression method. The population was 163 eighth-grade students, and the sample size was 42 students using proportionate stratified random sampling. The research instruments were a multicultural education questionnaire and a student tolerance attitude questionnaire, both of which were tested for validity and reliability. Data analysis was performed using SPSS version 27. The results of the study indicate a positive influence of multicultural education on students' tolerance attitudes with a significance value of 0.020 < 0.05. The coefficient of determination (R Square) value is 0.128, which means that multicultural education contributes 12.8% to students' tolerance attitudes, while 87.2% is influenced by other factors outside this study. The conclusion of this study is that multicultural education has an impact on increasing students' tolerance at SMP Negeri 16, Kupang City. Therefore, the school, subject teachers, and guidance and counseling teachers are expected to integrate multicultural values ​​into the learning process and counseling services, thereby creating an inclusive, harmonious, and respectful learning environment for differences.